2010
DOI: 10.1080/09602011003737087
|View full text |Cite
|
Sign up to set email alerts
|

Strength in numbers: Combining neck vibration and prism adaptation produces additive therapeutic effects in unilateral neglect

Abstract: Unilateral neglect is a multifaceted disorder. Many authors have, for this reason, speculated that the best treatment for neglect will involve combinations of different therapeutic techniques. Two well known interventions, neck vibration (NV) and prism adaptation (PA), have often been considered to be among the most effective treatments for neglect. Here, two experiments were performed to explore possible additive benefits when these interventions are used in combination to treat chronic neglect. Both experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 63 publications
0
46
0
1
Order By: Relevance
“…Fifteen additional RCTs investigating neglect were found that were not included in those reviews (prism adaptation, 2; virtual reality, 2; limb activation, 2; neck vibration with prism adaptation, 1; visual scanning with limb activation, 1; mental practice, 1; repetitive transcranial magnetic stimulation, 4; and optokinetic stimulation, 2). [471][472][473][474][475][476][477][478][479][480][481][482][483] There is evidence for the efficacy of several top-down and bottom-up approaches in improving both immediate performance and long-term performance on standard neglect tests such as cancellation tests and line bisection tests. * These include half-field eye patching, visual scanning training, prism adaptation, limb activation, optokinetic stimulation, mental imagery (but see the work by Welfringer and colleagues 482 ), and brain stimulation with repetitive transcranial magnetic stimulation, theta burst transcranial magnetic stimulation, or tDCS.…”
Section: Hemispatial Neglect or Hemi-inattentionmentioning
confidence: 99%
“…Fifteen additional RCTs investigating neglect were found that were not included in those reviews (prism adaptation, 2; virtual reality, 2; limb activation, 2; neck vibration with prism adaptation, 1; visual scanning with limb activation, 1; mental practice, 1; repetitive transcranial magnetic stimulation, 4; and optokinetic stimulation, 2). [471][472][473][474][475][476][477][478][479][480][481][482][483] There is evidence for the efficacy of several top-down and bottom-up approaches in improving both immediate performance and long-term performance on standard neglect tests such as cancellation tests and line bisection tests. * These include half-field eye patching, visual scanning training, prism adaptation, limb activation, optokinetic stimulation, mental imagery (but see the work by Welfringer and colleagues 482 ), and brain stimulation with repetitive transcranial magnetic stimulation, theta burst transcranial magnetic stimulation, or tDCS.…”
Section: Hemispatial Neglect or Hemi-inattentionmentioning
confidence: 99%
“…The association of complementary methods has been considered for SN rehabilitation in non-randomized studies drawing attention to longterm effects, thereby suggesting a synergy between different strategies [51,83,84]. Cumulative effects have also been achieved by associating PA with vibratory stimulation of the muscles at the back of the neck [85]. Future investigations should help clarify which associations are the most effective and how to select them according to the symptomatic and anatomic profiles of each patient.…”
Section: Discussionmentioning
confidence: 98%
“…A therapeutic approach which attacks both these aspects could be much more effective (e.g. Saevarsson, Kristjánsson, & Halsband, in press). …”
Section: Introductionmentioning
confidence: 99%